An Approach to the Classification of Apparent Asphyxial Infant Deaths. Issue 2 (June 2017) - Matshes, Evan W.; Lew, Emma O.
Recent evidence indicates that with thorough, high quality death investigations and autopsies, forensic pathologists have recognized that many unexpected infant deaths are, in fact, asphyxial in nature. With this recognition has come a commensurate decrease in, and in some cases, abolition of, the label "sudden infant death syndrome" (SIDS). Current controversies often pertain to how and why some infant deaths are determined to be asphyxial in nature and whether or not apparent asphyxial circumstances are risk factors for SIDS, or rather, harbingers of asphyxial deaths. In an effort to sidestep these controversies, some forensic pathologists elected to instead use the noncommittal label "sudden unexpected infant death" (SUID), leading to the unfortunate consequence of SUID – like SIDS – gaining notoriety as an actual disease that could be diagnosed, studied, and ultimately cured. Although it is not possible to provide death certification guidance for every conceivable type of unexpected infant death, we recognize and propose a simple classification system for overarching themes that cover the vast majority of cases where infants die suddenly and unexpectedly.